COGNITIVE IMPAIRMENT AND ITS ASSOCIATION TO RESOURSE USE AND COSTS IN RESIDENTS IN SWEDISH NURSING HOMES. (11th November 2018) - Sköldunger, A; Wimo, A; Sjögren, K; Björk, S; Backman, A; O Sandman, P
Abstract: We aimed to investigate resource use and its association to cognitive impairment, activities of daily living and neuropsychiatric symptoms in residents of Swedish nursing homes. Data was collected in 2014 from a Swedish national sample of nursing home residents (n=4 831) by proxies. The sample consists of all nursing homes in 35 of 290 randomly selected Swedish municipalities. Mean age was 85 years and 67% were women. Cognitive impairment was associated with a 23 hour per week increase in total resource use versus cognitively intact persons. This was also the case for being dependent in activities of daily living. Being dependent increased the amount of resource use by twenty-five hours per week. The sex of a resident did not influence the resource use. Cognitive impairment and functional dependency increases resource use significantly in nursing homes implying possibilities for differentiation of costs in institutional settings.